LANGUAGE AND MIGRATION: LANGUAGE TRANSFORMATION IN IMMIGRANT COMMUNITIES - Axatova Mohinisoxon Hasan qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article analyzes the processes of language and migration, specifically the key factors and mechanisms of language transformation in immigrant communities. It examines the new linguistic environments created as a result of migration, language change, bilingual or multilingual situations, as well as the social and cultural adaptation of immigrant communities. The study highlights the connection between language and social environment, the influence of language change on group identity, and its role in communicative processes.